Physiological Monitoring and Hearing Loss: Toward a More Integrated and Ecologically Validated Health Mapping. (November 2020) - Caduff, Andreas; Feldman, Yuri; Ben Ishai, Paul; Launer, Stefan
Abstract : With an ongoing shift from managing disease toward the inclusion of maintaining health and preventing disease, the world has seen the rise of increasingly sophisticated physiological monitoring and analytics. Innovations range from wearables, smartphone-based spot monitoring to highly complex noncontact, remote monitoring, utilizing different mechanisms. These tools empower the individual to better navigate their own health. They also generate powerful insights towards the detection of subclinical symptoms or processes via existing and novel digital biomarkers. In that context, a topic that is receiving increasing interest is the modulation of human physiology around an individual "baseline" in everyday life and the impact thereof on other sensorineural body functions such as hearing. More and more fully contextualized and truly long-term physiological data are becoming available that allows deeper insights into the response of the human body to our behavior, immediate environment and the understanding of how chronic conditions are evolving. Hearing loss often goes hand in hand with chronic conditions, such as diabetes, cognitive impairment, increased risk of fall, mental health, or cardiovascular risk factors. This inspires an interest to not only look at hearing impairment itself but to take a broader view, for example, to include contextualized vital signs. Interestingly, stress and its physiological implications have also been shown to be a relevant precursor to hearing loss and other chronic conditions. This article deduces the requirements for wearables and their ecosystems to detect relevant dynamics and connects that to the need for more ecologically valid data towards an integrated and more holistic mapping of hearing characteristics.